Risk Sharing and Industrial Specialization: Regional and International Evidence - Kalemli-Ozcan, Sebnem; Sørensen, Bent E; Yosha, Oved (American Economic Review, 2003)
Risk Sharing and Industrial Specialization: Regional and International Evidence by Sebnem Kalemli-Ozcan, Bent E. Sørensen and Oved Yosha. Published in volume 93, issue 3, pages 903-918 of American Economic Review, June 2003